Committed Emissions of the U.S. Power Sector, 2000–2018. Issue 3 (3rd September 2020) - Shearer, Christine; Tong, Dan; Fofrich, Robert; Davis, Steven J.
Abstract: Annual carbon dioxide (CO2 ) emissions from the U.S. power sector decreased 24% from 2000 to 2018, while carbon intensity (CO2 per unit of electricity generated) declined by 34%. These reductions have been attributed in part to a shift from coal to natural gas, as gas‐fired plants emit roughly half the CO2 emissions as coal plants. To date, no analysis has looked at the coal‐to‐gas shift from the perspective of commitment accounting—the cumulative future CO2 emissions expected from power infrastructure. We estimate that between 2000 and 2018, committed emissions in the U.S. power sector decreased 12% (six GtCO2 ), from 49 to 43 GtCO2, assuming average generator lifetimes and capacity factors. Taking into consideration methane leakage during the life cycle of coal and gas plants, this decrease in committed emissions is further offset (e.g., assuming a 3% leakage rate, there is effectively no reduction at all). Thus, although annual emissions have fallen, cumulative future emissions will not be substantially lower unless existing coal and gas plants operate at significantly lower rates than they have historically. Moreover, our estimates of committed emissions for U.S. coal and gas plants finds steep reductions in plant use and/or early retirements are already needed for the country to meet its targets under the Paris climate agreement—even if no new fossil capacity is added. Plain Language Summary: The substitution of natural gas for coal plants has been promoted as a way to lower greenhouse gas emissions, because CO2 emissions per unit electricity generated from gas are roughly half that of coal. The potential for such coal‐to‐gas reductions is demonstrated by the U.S. power sector, where increased use of natural gas for electricity generation has occurred alongside substantial reductions in annual CO2 emissions. However, changes in annual emissions are only part of the story; such reductions have been accompanied by large changes in the age and composition of the U.S. generating fleet. These infrastructure changes are reflected in an accounting of "committed" emissions or the emissions that are expected to occur over the entire operating life of power plants. We find that although annual emissions from power plants decreased by 24% between 2000 and 2018, committed emissions decreased by only 12%, as coal plants at the end of their operating lifetime were replaced by new gas plants with potentially long operating lifetimes. We find that very large reductions in the use of U.S. coal and gas plants are already needed for the country to meet its targets under the Paris climate agreement—even if no new coal or gas plants are built. Key Points: While CO2 emissions in the U.S. power sector fell 24% from 2000 to 2018, total committed emissions decreased by only 12% Coal plants from 2000 to 2018 retired at a capacity‐weighted average of 50 years, limiting reductions in committed emissions from early closure Committed emissions from coal and gas plants are incompatible with U.S. climate goals barring a significant reduction in historic usage